Pengaruh Merek dan Saluran Distribusi terhadap Volume Penjualan Perusahaan Otomotif - Ika Kartika; Vanessa Vicario (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
Every company generally has a brand that serves as its unique identity and plays a crucial role in driving sales growth. In addition, accurate and effective distribution channels can also increase a company’s sales volume. This study aims to examine the influence of brand and distribution channels on the sales volume of an automotive company. The research employs a quantitative approach using both primary and secondary data. The population of this study consists of 37 respondents, all of whom were selected using a saturated sampling technique, meaning that the entire population was used as the research sample. The variables were measured using a Likert scale to obtain quantitative data. Data analysis was conducted using multiple linear regression to determine the effect of the independent variables on the dependent variable. The results indicate that, simultaneously, brand and distribution channels have a significant effect on sales volume at PT. DSE. Partially, the brand variable has a significant influence on sales volume, while distribution channels also contribute positively and significantly. These findings suggest that strengthening brand strategies and managing distribution channels effectively are essential for increasing sales volume and enhancing the company’s competitiveness.